Insight into the structure, function and conjugative transfer of pLPU83a, an accessory plasmid of Rhizobium favelukesii LPU83 - Castellani, Lucas G.; Nilsson, Juliet F.; Wibberg, Daniel; Schlüter, Andreas; Pühler, Alfred; Brom, Susana; Pistorio, Mariano; Torres Tejerizo, Gonzalo (Plasmid, 2019)
Plasmids are widely distributed in rhizobia, a group of bacteria able to establish symbiotic relationships with the roots of legume plants. Two types of conjugative transfer (CT) regulation of these elements have been described in more detail. The most prevalent is through Quorum-Sensing (QS), mediated by the interaction of the TraR regulator protein and its cognate acyl-homoserine lactone (AHL) synthesized by TraI. In this study, we analyzed rhizobial plasmids classified according to their TraR regulators into four different groups. Each group has a particular genomic architecture. In one of the groups (I-C), represented by pLPU83a from Rhizobium favelukesii LPU83, CT induction requires TraR. With manual annotation, a traI was located in the plasmid distant to the traR gene. These features make pLPU83a an interesting plasmid for studying novel mechanisms of CT regulation. We mutagenized the traI gene, and found that it does not participate in CT regulation. Furthermore, we studied whether pLPU83a is subject to QS regulation by determining CT at different growth stages (cell densities). Our results showed no positive correlation between increase in culture densities and CT induction, on the contrary a slight decrease in CT was found at higher culture densities, unlike other TraR-depending plasmids. Our results show that transfer of pLPU83a is not regulated in a QS-dependent manner, and suggest that molecules not yet identified may activate its CT. Also, accumulation of a putative inhibitor cannot be disregarded. •The TraR phylogeny shows four groups that also share genetic organization of the conjugative transfer genes.•In spite of depending on a TraR, pLPU83a conjugative transfer does not require the plasmid-encoded TraI.•Quorum-Sensing does not mediate conjugative transfer of plasmid pLPU83a.•The conjugative transfer frequency of plasmid pLPU83a had a slight but significant decrease at higher culture densities.